Assessing the relationship between pigs’ stress resilience and their behavior in response to weaning - Lee, Bora; Luttman, Andrea M.; Ernst, Catherine W.; Raney, Nancy E.; Oh, Soyeong; Siegford, Janice M. (Frontiers in Animal Science, 2024)
IntroductionAs pigs are exposed to multiple stressors in production systems, we must understand their ability to be resilient to a range of environmental challenges to maintain production and welfare. Stress-resilience (SR) is the capacity to cope with and recover from stressors while maintaining healthy emotional functioning. In contrast, stress-vulnerability (SV) contributes to and predicts the onset and persistence of mood disorders and pathological processes following exposure to stress.Methods52 focal gilts were identified through a physiological marker (cortisol) in a previous study to compare resilience to weaning stress and behavioral responses at weaning. Within pigs’ home pen, we observed agonistic behavior, non-agonistic social behavior, and daily maintenance behaviors. Behavior was observed over two 4-hour periods (6 AM to 10 AM): one (D1) and four days post-weaning (D4).ResultsOn D1, SV pigs displayed a higher average frequency of non-injurious contact behavior (P = 0.0198) compared to SR pigs, while SR pigs exhibited a significantly longer average duration of lying behavior (P = 0.018) compared to SV. On D4, SV pigs exhibited a significantly longer duration of fighting behavior (P = 0.025) on average compared to SR pigs. Additionally, a significant effect of time on behavioral adaptation patterns was observed. On D1 post-weaning, pigs spent more time fighting (P < 0.001) and exploring (P < 0.001) and showed more frequent non-injurious contact (P = 0.029) and drinking behaviors (P < 0.001) compared to D4. Conversely, on D4, pigs spent more time feeding (P = 0.005) and lying (P < 0.001) compared to D1.DiscussionOur findings imply that non-injurious contact and lying behaviors immediately after weaning and fighting behavior several days later may be promising indicators of pigs’ ability to be resilient to the stress associated with weaning. However, to better understand how pigs change their behavior in response to the stress of weaning, we need standard approaches for measuring their behavior and evaluating the degree of change. Understanding behavioral variation between SR and SV pigs can facilitate the development of resilience indexes that could be helpful in breeding programs, facilitating the selection of resilient pigs that overcome challenges associated with weaning.